Low FODMAP Diet and Probiotics in Irritable Bowel Syndrome: A Systematic Review With Network Meta-analysis - Chao-Rong Xie; Bin Tang; Yun-Zhou Shi; Wen-Yan Peng; Kun Ye; Qing-Feng Tao; Shu-Guang Yu; Hui Zheng; Min Chen (Frontiers Media S.A., 2022)
Background: Probiotic and low fermentable oligosaccharide, disaccharide, monosaccharide, and polyol (FODMAP) diet are two commonly used management approaches for patients with irritable bowel syndrome (IBS). We aimed to evaluate the most effective combinations and components among different probiotics or low FODMAP diet through component network meta-analysis (NMA).Methods: We searched Embase, Ovid Medline, and Web of Science from inception to 21 January 2021. Randomized controlled trials (RCTs) examining the efficacy of probiotics and low FODMAP diet for IBS were included, with placebo, sham diet, or conventional treatments as controls. Binary outcomes were compared among treatments using the relative ratio (RR). A minimally contextualized framework recommended by the GRADE group was used to evaluate the certainty of evidence. The primary efficacy outcome was the relief of global IBS symptoms, and the secondary efficacy outcome was the reduction in IBS symptom scores or abdominal pain scores.Key Results: We included 76 RCTs (n = 8058) after screening 1940 articles. Eight RCTs were classified as low risk of bias. Standard network meta-analysis (NMA) showed that Lactobacillus (RR 1.74, 95% CI 1.22-2.48) and Bifidobacterium (RR 1.76, 95% CI 1.01-3.07) were the most effective for the primary efficacy outcome (high certainty evidence); component NMA showed that Bacillus (RR 5.67, 95% CI 1.88 to 17.08, p = 0.002) and Lactobacillus (RR 1.42, 95% CI 1.07 to 1.91, p = 0.017) were among the most effective components. The results of standard NMA and CNMA analysis of the improvement of overall IBS symptom scores or abdominal pain scores were consistent with this finding.Conclusion:Lactobacillus was the most effective component for the relief of IBS symptoms; Bifidobacterium and Bacillus were possibly effective and need further verification.Systematic Review Registration: website, identifier registration number.